Hukum Cryptocurrency sebagai Mata Uang dan sebagai Komoditas (Analisis Fatwa MUI tentang Hukum Cryptocurrency) - Abdillah, Hilmi (Jurnal Ilmiah Ekonomi Islam, 2023)
The decision of the Ijtima Ulama of the VIIth Indonesian Fatwa Commission of the Indonesian Ulema Council (Majelis Ulama Indonesia) in 2021 considers cryptocurrency as a digital currency and also as a commodity or tradable asset. However, there are differences in the law of cryptocurrency as a currency and as a commodity. This research will elaborate on the analysis of legal sources and legal ‘illat used in the fatwa and the reasons why there are legal details in the fatwa. This research includes qualitative research in the form of library research. The data analysis technique used in this research is descriptive-analytical with a normative juridical approach to Islamic law. The legal differentiation that occurs in the status of cryptocurrency as a currency and as a commodity is also inseparable from the provisions of an object that can be used as currency (naqd) and commodity (sil’ah). If cryptocurrency is considered a currency, then the law is absolutely haram, while as a commodity, the law is permissible when it meets the conditions that have been mentioned.